The Plecoptera of Panama. II. Two new species, one new country record, and additional locality records of Anacroneuria (Perlidae) from western Panama - Stark, Bill P.; Armitage, Brian J. (Zootaxa, 2018)
Two new species of Anacroneuria (A. chiriqui sp. n. and A. ngabe sp. n.) are described from Chiriqui Province, Panama, and compared with related species. One new country record, A. divisa (Navás), is herein recorded and new locality records are presented for several species previously reported from Panama. Three unassociated females, including one species from Bocas del Toro province are described under informal designations. There are now 25 described species of Plecoptera known from Panama.